A Comparison of Anterior and Posterior Lumbar Interbody Fusions: Complications, Readmissions, Discharge Dispositions, and Costs. Issue 24 (15th December 2017) - Qureshi, Rabia; Puvanesarajah, Varun; Jain, Amit; Shimer, Adam L.; Shen, Francis H.; Hassanzadeh, Hamid
Abstract : Study Design: Retrospective database review. Objective: To understand medical complication rates, readmission rates, costs, and discharge dispositions in anterior lumbar interbody fusion (ALIFs) versus transforaminal lumbar interbody fusions (TLIFs)/posterior lumbar interbody fusions (PLIFs) for lumbar degenerative disease. Summary of Background Data: Indications for ALIFs versus PLIFs can vary, though benefits of anterior approach surgery include full access to the anterior column and ability to place fusion devices. Methods: The PearlDiver Database of Medicare records was utilized for this retrospective database review. A study group consisting solely of ALIF procedure patients was selected for. Similarly, a TLIF/PLIF group was selected for. Both groups were queried for comorbidities, 30 and 90-day complication and readmission rates. Additionally, discharge dispositions, and in-hospital/30-day/90-day Medicare reimbursements were determined. Results: At both 30 and 90 days postoperatively odds of ileus, wound infection, and lower extremity deep venous thrombosis were significantly increased in the ALIF. However, unadjusted rates and adjusted odds of transfusion or dural tear were significantly decreased in the ALIF patients. Odds of 30-day readmission were 4 times higher in ALIF patients. Additionally, 30 and 90-day total costs of care in ALIF patients were significantly increased by approximately 4800 and 5800 respectively, as compared with patients undergoing TLIF/PLIF. Conclusion: Despite higher initial routine discharge rates, readmissions and costs of postoperative care were significantly increased in ALIF procedures. It is necessary to evaluate etiology of degenerative pathology as ALIFs are successful solutions to anterior translational instability and anterior disc slippage, but may not have the best long-term outcomes and may not be cost-effective compared with a TLIF/PLIF. In light of our data, it is important to assess the risks and benefits of the varying approaches, and the necessity to access the anterior column, when deciding on surgical technique to treat lumbar degenerative pathology. Level of Evidence: 4